2022
DOI: 10.1161/jaha.120.020450
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to a High‐Salt Diet Is Sex Dependent

Abstract: Background Premenopausal women are less likely to develop hypertension and salt‐related complications than are men, yet the impact of sex on mechanisms regulating Na + homeostasis during dietary salt challenges is poorly defined. Here, we determined whether female rats have a more efficient capacity to acclimate to increased dietary salt intake challenge. Methods and Results Age‐matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 69 publications
7
19
0
Order By: Relevance
“…Our results revealed sex and genotypic differences in urinary ET-1 excretion ( Figure 3 ). Among WT mice, females excreted significantly more ET-1 compared to males ( Figure 3 ), which is consistent with recent reports in rats and humans ( Gohar et al, 2022 ). Interestingly, female GPER1 KO mice excreted significantly lower levels of urinary ET-1 compared to female WT littermates ( Figure 3 ), suggesting that GPER1 contributes to the sex difference in urinary ET-1 excretion.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our results revealed sex and genotypic differences in urinary ET-1 excretion ( Figure 3 ). Among WT mice, females excreted significantly more ET-1 compared to males ( Figure 3 ), which is consistent with recent reports in rats and humans ( Gohar et al, 2022 ). Interestingly, female GPER1 KO mice excreted significantly lower levels of urinary ET-1 compared to female WT littermates ( Figure 3 ), suggesting that GPER1 contributes to the sex difference in urinary ET-1 excretion.…”
Section: Resultssupporting
confidence: 92%
“…In outer and inner medullary tissues, female mice regardless of their genotype have increased ET-1 peptide content than males. These results support previous evidence (Nakano and Pollock, 2009;Jin et al, 2013;Johnston et al, 2016;Gohar et al, 2020;Gohar et al, 2022) that females have greater ET-1 activity than males. Furthermore, our results reveal that GPER1 deletion increases outer medullary ET-1 mRNA expression and ET-1 protein content in females but not males.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Prior studies in both rats and humans have demonstrated that females are more efficiently and rapidly able to excrete an acute salt load. 35,36 Gohar et al 36 recently reported that female rats can acclimate to HS diets more rapidly than males along with evidence for additional mechanisms for achieving salt balance compared with males.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other models of salt sensitivity show that males have a more severe phenotype to high salt diets and so this highlights the complexity and wider array of mechanisms that contribute to the mechanisms of sodium homeostasis. 9 , 10 …”
Section: A Perspective On 'Endothelial Cullin3 Mutation Impairs Nitri...mentioning
confidence: 99%